IFS Supplement on Monetary and Financial Statistics. (International Financial Statistics; Vol. 61, Sept. 2008, 2008)
This paper discusses the report on International Financial Statistics (IFS) Supplement on Monetary and Financial Statistics. Issued in three parts, this annual publication contains balance of payments and international investment position data. Part 1 of this report provides detailed tables on balance-of-payments statistics for approximately 171 countries and international investment position data for 111 countries. Part 2 of this quarterly report presents tables of regional and world totals of major balance-of-payments components. Part 3 of this IFS report contains descriptions of methodologies, compilation practices, and data sources used by reporting countries. Quarterly issues of this publication provide, for 158 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. In addition, similar summary tables for the world, industrial countries, and developing countries are included. The Statistics Department of the Fund is pleased to make available to subscribers the IFS database through an easy-to-use online service.